(untitled) (Research, Society and Development, 2020)
This study aimed to structure a skills development program, based on the learning trail system, for intermediate level managers of the Institutional Development Dean’s Office (PRODIN) of the Catarinense Federal Institute - IFC. This research was applied, predominantly qualitative, being classified as descriptive. It presented characteristics of a bibliographic, documentary research, field research and case study. For data collection, in addition to documentary and bibliographic analysis, semi-structured interviews and questionnaires were used. Data analysis took place through content analysis. As a result, the skills required of PRODIN / IFC intermediate managers were identified and classified and divided into four categories: intellectual, interpersonal; technical and intrapersonal. After checking the degree to which each competency is required, it was realized that all categories analyzed by the interviewees are strongly required. In this way, it is possible to affirm that the inferred managerial competences were validated by the IFC managers, as well as, they were included in the structuring of the development program by competence. In order to structure the proposed program, the reality of the researched institution was considered, with a view to effectively contributing to the development of PRODIN - IFC managers.